Penanaman Sikap Sosial dan Emosional Melalui Pembelajaran IPAS Pada Siswa Kelas IV SD Negeri 2 Ambon: Indonesia - Arista, Eka; Mahananingtyas, Elsinora; Ritiauw, Leonid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is to describe the process of planting social and emotional attitudes of students in the fourth grade of SD Negeri 2 Ambon. The method used in this study is Quantitative with survey approach. Meanwhile, data collection techniques using questionnaires or questionnaires. The results showed that in general the social and emotional attitudes of students are in the good category. On the aspect of social attitudes, the majority of students showed good cooperation, good manners towards teachers and friends, a sense of responsibility in the group, an open attitude towards differences, and active participation in discussion activities and group projects.